Do Corporate Social Responsibility and Corporate Governance Disclosures Affect Tax Avoidance? - Faradila Dyah Ayu Widianti; Andrian Budi Prasetyo (Universitas Negeri Semarang, 2023)
Purpose: The purpose of this study is to examine the impact of corporate social responsibility (CSR) and corporate governance on tax avoidance. Method: This empirical study uses a database from Bloomberg within all companies listed on Indonesia Stock Exchange excluding this sector: finance; property and real estate. The initial sample includes 25 companies with 5 years of observation from 2017 to 2021 and in total there are 125 research samples. In order to test the impact of CSR and corporate governance on tax avoidance, this research uses multiple linear regression. Findings: The result shows that CSR disclosure increases tax avoidance which indicates that there is a trade-off between CSR disclosure and tax. But this research design does not find evidence that corporate governance has an impact on tax avoidance which means that corporate governance can not mitigate tax avoidance. Novelty: Some previous research based on GRI Index for measuring CSR and using some proxy such as board independence, audit quality, audit committee for measuring corporate governance. This study using Environmental and Social Disclosure Score for measuring Practice of CSR and using Governance Disclosure Score for measuring Corporate Governance.